Investigating above‐ground biomass in old‐growth and secondary montane forests of the Cameroon Highlands. (30th January 2020) - Ngute, Alain Senghor K.; Sonké, Bonaventure; Nsanyi Sainge, Moses; Calders, Kim; Marchant, Rob; Cuni‐Sanchez, Aida
Abstract: Tropical montane forests can store and sequester substantial amounts of carbon in above‐ground biomass (AGB), but variations in this storage related to location or degradation have not been quantified in the Cameroon Highlands. We established 25 permanent plots (20 m × 40 m) and sampled all trees ≥10 cm diameter following standard RAINFOR protocols. We estimated AGB and investigated variations related to taxonomic and structural forest attributes, including the height–diameter allometry in five forest types (four old‐growth dominated by different species and one secondary forest). Secondary forests had significantly lower AGB than old‐growth forests (49.4 ± 2.5 vs. >476.3 ± 168.7 Mg/ha, respectively), mostly related to lower basal area and tree height. Significant differences in species composition but not in forest structure or AGB were found between the four types of old‐growth forests studied, located at different altitudes and mountains. We discuss the importance of these montane forests for carbon storage and, considering their high diversity and current threats, their potential for carbon finance mechanisms related to both avoided deforestation and forest restoration. Résumé: Les forêts tropicales montagnardes peuvent stocker et séquestrer des quantités substantielles de carbone dans la biomasse aérienne, mais les variations de ce stockage liées à l'emplacement ou à la dégradation n'ont pas été quantifiées dans les hautes terres du Cameroun. Nous avons établi 25 parcelles permanentes (20 m × 40 m) et échantillonné tous les arbres ≥10 cm de diamètre, suivant les protocols standards du RAINFOR. Nous avons estimé la biomasse aérienne et étudié les variations liées aux attributs taxonomiques et structurels de la forêt, y compris l'allométrie hauteur‐diamètre dans cinq types de forêts (quatre forêts anciennes dominées par différentes espèces et une forêt secondaire). Les forêts secondaires avaient un AGB significativement plus faible que les forêts anciennes (49.4 ± 2.5 vs. >476.3 ± 168.7 Mg/ha, respectivement), principalement liées à la surface terrière reduite et faible hauteur des arbres. Des différences significatives dans la composition specifique, mais pas dans la structure forestière non plus dans la biomasse aérienne, ont été observées entre les quatre types de forêts anciennes étudiées, en outré situées à différentes altitudes et montagnes. Nous discutons de l'importance de ces forêts de montagne pour le stockage du carbone et, compte tenu de leur grande diversité et des menaces actuelles, de leur potentiel pour les mécanismes de financement du carbone liés à la fois à la réduction de la déforestation et à la restauration des forêts. Mots clés: Montagnes africaines; structure forestière; allométrie hauteur‐diamètre; diversité arboricole